2011
DOI: 10.1097/qad.0b013e3283471efa
|View full text |Cite
|
Sign up to set email alerts
|

Understanding disparities in HIV infection between black and white MSM in the United States

Abstract: Less knowledge of partner HIV status and lower ART use among black MSM may partially explain differences in HIV infection between black and white MSM. Efforts to encourage discussions about HIV status between MSM and their partners and decrease barriers to ART provision among black MSM may decrease transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
138
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(143 citation statements)
references
References 22 publications
3
138
2
Order By: Relevance
“…18 A 2008 study that included multiple partner-level factors found that having a partner with an unknown HIV status was associated with HIV and was more commonly reported by black than white MSM. 19 Furthermore, black men are estimated to have the highest number of unidentified HIV infections, 20 and studies have found that minority MSM (black, Hispanic, mixed race) were more likely to be unaware of their HIV infection. [21][22][23] Additionally, access to antiretroviral therapy which has been associated with reduced HIV transmission 24 is lower among black MSM.…”
Section: Resultsmentioning
confidence: 99%
“…18 A 2008 study that included multiple partner-level factors found that having a partner with an unknown HIV status was associated with HIV and was more commonly reported by black than white MSM. 19 Furthermore, black men are estimated to have the highest number of unidentified HIV infections, 20 and studies have found that minority MSM (black, Hispanic, mixed race) were more likely to be unaware of their HIV infection. [21][22][23] Additionally, access to antiretroviral therapy which has been associated with reduced HIV transmission 24 is lower among black MSM.…”
Section: Resultsmentioning
confidence: 99%
“…[13][14][15][16][17] However, dismissal of sexual risk-related behavior as a contributing factor to racial disparities in HIV infection is premature in the absence of evidence derived from more precise and comprehensive behavioral measures. The lack of specificity typically involved in PAI-related risk measures clouds assessment of the actual level of risk averted.…”
mentioning
confidence: 99%
“…More specifically, the only significant difference was that Black MSM newly diagnosed with HIV were more likely to report that their last male partner had an unknown HIV status when compared to White MSM who were newly diagnosed. 24 However, the previous an increased risk of substance use and engagement in condomless anal intercourse (CAI). 25 Among a sample of YMSM, Stults et al found that IPV was associated with between a 1.8-2.5 greater odds of using stimulants 26 and a two-fold greater odds of condomless receptive anal sex.…”
Section: Introductionmentioning
confidence: 99%